PENGARUH MODEL PEMBELAJARAN THINK PAIR SHARE TERHADAP KEMAMPUAN MENGANALISIS CERPEN SISWA KELAS IX DI SMP NEGERI 5 ANGKOLA MUARATAIS - Siregar, Juliana (Jurnal Kesehatan Ilmiah Aufa Royhan, 2020)
This study aims to know whether there is a significant influence of using pair share learning model on students’ ability in analyzing short stories at the eleventh grade students of SMP Negeri 5 Angkola Muaratais. The research was conducted by applying experimental method (one group pretetst post test design) with 24 students as the sample and were taken by using random sampling technique from 192 students. Test and observation were used in collecting the data. Descriptive and inferential analyzes are used to analyzed the data. Based on the data analysis, it was found: (a) the average of using pair share learning model was 3.20 (good category) and (b) students’ ability in analyzing short stories before using pair share learning model was 61.6 (enough category) and after using pair share learning model was 79 (good category). Furthermore, based on inferential statistics by using paired sample ttest, the result showed ttable was less than tcalculated (1.714 > 11. 9). It means, there is a significant influence of using pair share learning model on students’ ability in analyzing short stories at the eleventh grade students of SMP Negeri 5 Angkola Muaratais.